Transforming Media Accessibility in Europe Digital Media, Education and City Space Accessibility Contexts - Marcus-Quinn, Ann.; Krejtz, Krzysztof; Duarte, Carlos; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
In a rapidly evolving digital landscape, accessibility in media has emerged as a crucial frontier for inclusion, equality, and knowledge democracy. The present edited volume "Transforming Media Accessibility in Europe: Digital Media, Education and City Space Accessibility Contexts" is a comprehensive exploration of technological, societal, psychological, and legal aspects of media accessibility in Europe. It offers a comprehensive roadmap for navigating the multifaceted landscape of media accessibility. Through compelling experimental studies, case studies, and forward-looking insights, it elucidates the transformative potential of accessible media across diverse sectors, including education, culture, and smart cities. Crafted as a collaborative effort under the COST (European Cooperation in Science and Technology) LEAD-ME Action (CA19142), this book unites the expertise of researchers, educators, and practitioners. This is an open access publication. .
Introduction -- Part 1: Outside the screen -- Accessibility in tourism 5.0 approach: Enabling inclusive and meaningful tourist experiences -- Accessibility in public transport by example of Warsaw -- Subjectivity and creativity vs. audio description guidelines -- Gaze-Led Audio Description (glad). Concept and application to accessibility of architectural heritage -- Establishing an accessible university for students with disabilities: Case study of The Aksaray University -- Part 2: Inclusive art and society -- Digital constitutionalism and the data economy -- Making copyright management agile: Challenges and opportunities in audiovisual translation and media accessibility for a new digital era -- The inclusivity of art in city space. Activities of researchers from the University of Lodz to support people with sensory disabilities: A case study from Lodz (Poland) -- Contemporary art and audio accessibility from translation studies- an essential binomial in current artistic creations -- Part 3: Learning and education -- An overview of media accessibility and inclusivity in the educational domain -- Media accessibility in education- combining bibliometric study and literature review -- Media accessibility in e-learning: Analyzing learning management systems -- Accessibility of ebooks for secondary school students in Ireland and Cyprus -- Examining the accessibility of online educational content - A case study of second-language learning videos -- Accessibility in technology-enhanced curricula - A comparative study in Portugal, Turkey, and Lithuania -- Cognitive accessibility in educational games - A set of recommendations -- Enabling digital literacy pedagogical sessions: A case study from Portugal -- Exploring the potential of media accessibility as a pedagogical tool: Students as audio describers -- Assessing the impact of assistive technologies on the lives of the hearing impaired: A bibliometric analysis -- Part 4: Technological innovations for accessibility -- Academic training in media accessibility in audiovisual translation at a university level: The case of the Spanish university system -- Digital media tools for accessibility and inclusion: A case study from the Ukraine -- A multimodal approach for improving a dialogue agent for therapeutic sessions in psychiatry -- Control the stream of sounds: A pilot study on intersemiotic translation of sound effects and music for subtitling for the d/deaf and hard of hearing in German, Spanish and English in VOD platforms.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: User interfaces (Computer systems).; Human-computer interaction; People with disabilities -- Education; Interactive multimedia; Multimedia systems; User Interfaces and Human Computer Interaction; Education and Disability; Media Design